Transnational Pathways to English Higher Education - Ilieva, Janet (International Higher Education, 2015)
This article studies international students who transfer from transnational education (TNE) courses delivered overseas by UK higher education providers to first degree programmes in England. Transnational students accounted for an estimated 34 per cent of the total international first degree entrants in England in 2012-13. Our analysis shows that transnational students have mitigated declines in direct entry of international students to first degree programmes in 2012-13 and were found to be a major contributor to postgraduate enrolments.